2015
DOI: 10.2147/ijn.s76168
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate-coated long-circulating liposomes containing 99mtechnetium-ceftizoxime used to identify osteomyelitis

Abstract: Osteomyelitis is a progressive destruction of bones caused by microorganisms. Inadequate or absent treatment increases the risk of bone growth inhibition, fractures, and sepsis. Among the diagnostic techniques, functional images are the most sensitive in detecting osteomyelitis in its early stages. However, these techniques do not have adequate specificity. By contrast, radiolabeled antibiotics could improve selectivity, since they are specifically recognized by the bacteria. The incorporation of these radioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…This suggests that ALD does not reach sufficient concentrations in tumours to be therapeutically efficacious as a monotherapy, even when encapsulated in a liposomal formulation. L-ALD has also been used in the treatment of inflammatory conditions [32] , [33] , [34] , [35] . The ability of ALD liposomes to deplete monocytes and macrophages has been shown to inhibit restenosis and endometriosis in a rat model [35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that ALD does not reach sufficient concentrations in tumours to be therapeutically efficacious as a monotherapy, even when encapsulated in a liposomal formulation. L-ALD has also been used in the treatment of inflammatory conditions [32] , [33] , [34] , [35] . The ability of ALD liposomes to deplete monocytes and macrophages has been shown to inhibit restenosis and endometriosis in a rat model [35] .…”
Section: Discussionmentioning
confidence: 99%
“…However, its use in vivo was prohibited by the profound toxicity and sudden mice death [23] , [29] . Several studies have reported the use of L-ALD for therapeutic applications in cancer [31] and inflammatory conditions [32] , [33] , [34] , [35] pre-clinically. L-ALD has been shown to be effective when used with Vγ9Vδ2 T cells in an ovarian cancer model in vivo [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternatives must be found in order to ensure an accurate diagnosis. In this sense, scintigraphic imaging is a promising approach since it is based on physiological changes, which occur earlier than anatomical modifications [ 2 4 ]. In this context, radiolabeled antimicrobial peptides have been investigated as possible suitable tools, since they accumulate in infectious sites instead of in aseptic inflammatory lesions, once they preferentially bind to bacteria and fungi [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of radioisotope as the last step of the synthesis is of interest for in vivo studies and clinical translation as it minimises loss of therapeutic efficacy due to decay of the isotope during protracted manufacture. This is a clear advantage in comparison to some previously published nanoparticle-radionuclide constructs where the time required for formulation exceeds the half-life of the radionuclide 44. Physico-chemical characterisation of liposomal formulations are presented in the Figure S1.…”
Section: Resultsmentioning
confidence: 99%